Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual, Budaya Organisasi dan Kinerja Karyawan - Ni Made Astri Septiarini; A.A.N. Eddy Supriyadinata Gorda (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThis research is aimed to examine the impact of intellectual intelligence, emotional intelligence, spiritual intelligence, to organizational culture and employee performance in Mulia Farma Group so later this research can be used to increase Mulia Farma Group employee performances. This research has been conducted in Mulia farma Group. The location is in Singaraja and 56 employees are taken as responden. Questionaire was used as a tool in data collection method. Data analysis techniques in this research are path analysis.  This research gets some important conclusion. Firstly, all hypothesis were proved to be significant. Secondly, all of variables intellectual intelligence, emotional intelligence spiritual intelligence, organizational culture has positive and significant impact on employee performance. Thirdly, the emotional intelligence has the greatest impact compare with other independent variables. The research implication is intellectual intelligence, emotional intelligence, spiritual intelligence, organizational culture played as important role in developing employee performance.